Motivations, tools, and theories of pre-modern science - Graubard, Mark (Burgess Pub. Co., 1967)
The result is that science is presented in our best educational institutions as the end result of a process, with little attention to the actual strucggle and search for scientific knowledge which man has pursued since his earliest history.